Upaya meningkatkan kesadaran masyarakat dalam menjaga kesehatan mata di masa pandemi Covid-19 - Purwanita, Purwanita; Amin, Ramzi; Sari, Prima Maya; Anggraini, Rika; Rosataria, Defayudina Dafilianty; Salim, Muhammad Usman (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
The SARS-CoV-2 virus is part of the coronavirus family. Currently, transmission of SARS-CoV-2 through droplet that come out when coughing, sneezing or contact is believed to be the main route of transmission of the virus. Eye involvement in cases of COVID-19 has been reported in several journals. Research in Hubei, China, reported that 12 out of 30 confirmed COVID-19 patients were accompanied by conjunctivitis. One of the COVID-19 positive patients with conjunctivitis in Italy detected SARS-CoV-2 RNA in an eye specimen which may be a potential source of infection. Several studies have emphasized that the eyes are a potential entry point for the virus and emphasize the importance of masks and eye protection. Until now, there is no vaccine or specific treatment to deal with COVID-19, so prevention is the best step to take. Lack of public knowledge in recognizing how the SARS-CoV-2 virus is transmitted so that they are less introspective and do not take precautions for virus infection. Educational videos regarding things that must be considered about the eyes during the COVID-19 pandemic can be a means of health promotion to prevent the spread of infection. This community service is expected to attract the attention of the public to get to know COVID-19 and increase public awareness of how much we should work together to reduce the transmission of this virus.